NATIONAL ROMANTICISM IN WALT WHITMAN POEMS - Arianto, Tomi (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2018)
Romanticism is often misunderstood as something genuine love and merely about romance. In fact, romanticism is an understanding of great ideas that also be delivered great ideas. The development of Romanticism delivered a new orientation that called National Romanticism by maintaining the freedom of individual, sovereignty, and independent of human rights. This study took data from three Walt Whitman poems; Patriotic, War Democracy, and Poem of America. Researcher was using the concept of interpretation to explore the meaning of poetry and the influence of romanticism in Whitman poetry. Researchers use Isaiah's theory in his book “the root of romanticism” to explore the influence of the romanticism idea on Whitman's poems. From the three samples of poetry, it is found that romanticism is very influential in Whitman poetry, especially the idea of romantic nationalism. Patriotic themes, nationalities and egalitarian concepts are reflected in Whitman's collection of